(untitled) (The Pakistan Development Review, 1981)
The book under review is a compendium of acticles by eminent economists including W. M. Corden, Amartya Sen, Ronald McKinnon, Deepak Lal and others. These economists who have had much experience with policy-making in developing countries evaluate the different policies undertaken by governments to facilitate industrial progress in the less developed countries. Of particular importance among these policies are those that deal with the balance of payments, exchange control, licensing, tariffs, quotas, etc. As noted by the editors the manufacturing sector has been largely responsible for industrial development; as such the subject matter of all the articles is related to this sector only.